Pendidikan Anak Usia Dini (PAUD) Dalam Pendekatan Psikologi Anak - Nabil, Nabil (Almarhalah | Jurnal Pendidikan Islam, 2017)
In the point of psychology, the phenomenon of early childhood education is a necessity. Because the development of the human brain at an early age (0 to 6 years) accelerates to 80% of the overall adult brain. Often the early age is often referred to as the golden age (golden age) in the development of human history. Maria Montessori said that this period is a sensitive period in which children easily receive stimuli from their environment. It is during this sensitive period that physical and psychological functions are matured so that the child is ready to respond and realize all the developmental tasks that are expected to appear in his daily behavior patterns.The conceptual foundation that underlies the importance of PAUD is the discovery of experts about child development, especially in the field of neuroscience and psychology. Growth and development of children can not be released by the development of brain structures. According to Wittrock there are three areas of brain development that experience rapid increase at an early age, namely the growth of dendritic fibers, the complexity of synaptic relationships, and division of nerve cells. The three brain regions are very important to develop from an early age, because at this age the three brain regions experience maximum development, which is 80% of the overall adult brain development. After children aged 6 years and older until adulthood, their development does not exceed 20%.